2021
DOI: 10.1021/acsami.1c02290
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Salts@Metal–Organic Frameworks: Remarkable Component to Improve Performance of Fabric Filters to Remove Particulate Matters from Air

Abstract: The elimination of particulate matters (PMs) from the air is very important for our sustainability. In this study, highly porous metal–organic frameworks (MOFs) like MIL-101 and UiO-67 were first modified, coated onto cotton, and applied in PM removal via filtration. Ionic salts (ISs) like CaCl2 and LiCl, after loading onto the MOFs, remarkably increased the PM removal efficiency. For example, CaCl2(20)@MIL-101/cotton shows 5.7 times the quality factor (QF, which is the most important parameter in filtration) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…This is agreeable with the ESI mechanism in PM removal with DEA-ZIF-8/EC. So far, ESIs have been often applied to interpret the removal of hazardous materials 69 including PMs 26,29,31,62,70 with MOFs. In summary, a large pore is not essential to capture large PMs because small interaction sites (like CO, NH, and NH 3 + , NO 3 − ) on PMs will be more than enough for effective ESIs with porous materials like ZIF-8 (with charge separation, at least in part).…”
Section: So Far Various Mofs Including Zif-8 Have Been Appliedmentioning
confidence: 99%
“…This is agreeable with the ESI mechanism in PM removal with DEA-ZIF-8/EC. So far, ESIs have been often applied to interpret the removal of hazardous materials 69 including PMs 26,29,31,62,70 with MOFs. In summary, a large pore is not essential to capture large PMs because small interaction sites (like CO, NH, and NH 3 + , NO 3 − ) on PMs will be more than enough for effective ESIs with porous materials like ZIF-8 (with charge separation, at least in part).…”
Section: So Far Various Mofs Including Zif-8 Have Been Appliedmentioning
confidence: 99%
“…Because millions of deaths annually are estimated to be caused by exposure to indoor and outdoor air pollution, the World Health Organization (WHO) considers air pollution to be the single largest environmental health risk 5 , 6 . Particulate matter (PM), a complex mixture of fine solid and liquid particles with various chemical compositions, is one of the primary air pollutants 1 , 7 . The small size and large surface area of PM 2.5 (aerodynamic size less than 2.5 µm) can penetrate deep into the human lungs and can be toxic, thus increasing morbidity and mortality 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, as research has progressed, the lack of mesoscale cavities has shown to impede the diffusion/adsorption of macromolecules (e.g. enzymes, drugs and particulate matter), [ 7–10 ] which severely restricts the expansion of ZIFs’ application. Thus, the incorporation of mesopores (2–50 nm) in parent ZIFs is crucial in order to meet the requirements of modern applications.…”
Section: Introductionmentioning
confidence: 99%